2023
DOI: 10.1002/adma.202312125
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Growth of High‐Quality Single‐Crystal Twisted Bilayer Graphene on Liquid Copper

Shan Liu,
Baizhe He,
Wei Yang
et al.

Abstract: Twisted bilayer graphene (TBG) generates significant attention in the fundamental research of 2D materials due to its distinct twist‐angle‐dependent properties. Exploring the efficient production of TBG with a wide range of twist angles stands as one of the major frontiers in moiré materials. Here, the local space‐confined chemical vapor deposition growth technique for high‐quality single‐crystal TBG with twist angles ranging from 0° to 30° on liquid copper substrates is reported. The clean surface, pristine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Liu et al reported another novel method for producing high-quality single-crystal tBLGs with twist angles ranging from 0° to 30° using a local space-confined CVD growth technique on liquid Cu substrates. 265 The schematic diagram of the local space-confined strategy is shown in Fig. 18d.…”
Section: Atomic Engineeringmentioning
confidence: 99%
“…Liu et al reported another novel method for producing high-quality single-crystal tBLGs with twist angles ranging from 0° to 30° using a local space-confined CVD growth technique on liquid Cu substrates. 265 The schematic diagram of the local space-confined strategy is shown in Fig. 18d.…”
Section: Atomic Engineeringmentioning
confidence: 99%
“…Recently, because of the unique properties of liquid Cu, self-aligned graphene nanoribbons with widths down to sub-10 nm and aspect ratios up to 387 were fabricated via a template-free CVD route. 12 In addition, the growth of single-crystal twisted bilayer graphene on liquid Cu was achieved, 13 exhibiting superior thermal stability and carrier mobility as high as 26,640 cm 2 V −1 s −1 . Overall, the dynamic and rheological nature of the liquid Cu enables the graphene islands to rotate, move, and align freely, which provides an important platform for the orientation control in the growth of single-crystal graphene.…”
mentioning
confidence: 99%